A World Worth Living—Can Artificial Intelligence Help to Reach the Goal? - Hans-Jörg Kreowski (Proceedings, 2022)
Artificial intelligence (AI) is an area of computer science that has received much attention in the public media, politics and economy. There is a worldwide expectation that AI will be a key technology for the future. In this short paper, I sketch and discuss whether the prospects and hopes are realistic from a technical point of view and under which conditions AI will contribute to the welfare of human beings.